Roads Less Traveled: Sexual Dimorphism and Mast Cell Contributions to Migraine Pathology - Loewendorf, Andrea I.; Matynia, Anna; Saribekyan, Hakob; Gross, Noah; Csete, Marie; Harrington, Mike (Frontiers in Immunology, 2016)
Migraine is a common, little understood, and debilitating disease. It is much more prominent in women than in men ( 2/3 are women) but the reasons for female preponderance are not clear. Migraineurs frequently experience severe comorbidities such as allergies, depression, irritable bowel syndrome and others; many of the comorbities are more common in females. Current treatments for migraine are not gender-specific, and rarely are migraine and its comorbidities considered and treated by the same specialist. Thus, migraine treatments represent a huge unmet medical need, which will only be addressed with greater understanding of its underlying pathophysiology. We discuss the current knowledge about sex differences in migraine and its comorbidities, and focus in on the potential role of mast cells in both. Sex-based differences in pain recognition and drug responses, fluid balance, and the blood brain barrier are recognized but their impact on migraine is not well studied. Further, mast cells are well recognized for their prominent role in allergies but much less is known about their contributions to pain pathways in general and migraine specifically. Mast cell-neuron bidirectional communication uniquely positions these cells as potential initiators and/or perpetuators of pain. Mast cells can secrete nociceptor sensitizing and activating agents such as serotonin, prostaglandins, histamine and proteolytic enzymes that can also activate the pain-mediating transient receptor potential vanilloid (TRPV) channels. Mast cells express receptors for both estrogen and progesterone that induce degranulation upon binding. Further, environmental estrogens such as Bisphenol A activate mast cells in preclinical models but their impact on pain pathways or migraine is understudied. We hope that this discussion will encourage scientists and physicians alike to bridge the knowledge gaps linking sex, mast cells and migraine to develop better, more comprehensive treatments for migraine patients.